The effects of isolated game elements on adherence rates in food response inhibition training - Alexander MacLellan; Charlotte R. Pennington; Natalia Lawrence; Samuel J. Westwood; Andrew Jones; Anna Slegrova; Beatrice Sung; Louise Parker; Luke Relph; Jessica O. Miranda; Maryam Shakeel; Elizavet Mouka; et al. (Royal Society Open Science)
Food response inhibition training (food-RIT) is found to aid weight loss and reduce snacking of foods high in sugar, salt and fat. However, these interventions suffer from a lack of adherence, with gamification proposed as a solution to increase engagement. The effect of gamification is unclear, however, with a lack of research investigating the effects of single game elements in improving adherence to interventions. This study investigates whether isolated game elements (social or feedback) improve adherence, engagement and effectiveness of food-RIT compared to a standard non-gamified intervention. Two hundred and fifty-two participants (169 female) were randomly assigned to either non-gamified F-RIT, a training gamified with feedback elements or a training gamified with social elements. Participants completed measures of snacking frequency and food evaluation before and after a 14-day training period, with adherence and motivation recorded during this time. There were no significant effects of adding either feedback or social gamification elements on training adherence, motivation or effectiveness. There was no meaningful support for adding isolated game elements to food-RIT to improve intervention adherence, raising questions about the magnitude of simple gamification effects. Future research may benefit from systematically assessing the combined effects of multiple gamification elements.